1768 Safety culture and risk management in agriculture (sacurima). (24th April 2018) - Mc Namara, John; Leppälä, Jarkko; van der Laan, Gert; Colosio, Claudio; Jakob, Martina; Vander Broucke, Stephan; Girdziute, Laura; Merisalu, Eda; Marie Heiberg, Anne; Rautiainen, Risto
Abstract : Introduction: Agriculture is one of the most hazardous industries in Europe, measured by work-related injuries, diseases, disabilities and deaths. Statistics and studies show great differences in national injury and occupational disease rates, as well as approaches and support for prevention of these adverse outcomes. This EU-COST action explores reasons why agriculture lags behind other sectors, and why some countries have been more successful than others in reducing agricultural injuries and diseases. Methods: Evaluation of health and safety programmes and approaches on the national level identification of knowledge, attitudes, behaviors and priorities among farmers regarding safety, health and risk management identification of effective measures for training and integrating vulnerable populations (including refugees) into the agricultural workforce development of indicators for monitoring progress and evaluating the impact of interventions on occupational injuries and diseases in agriculture. Results: Benchmarked and evidence-based recommendations will be developed to inform and guide national initiatives and efforts. Results will be disseminated to stakeholders and the agricultural community. Discussion: This action is in progress; previous Cooperation in Science and Technology (COST) Actions, like Monitoring Occupational Diseases and tracing New and Emerging Risks in a Network (MODERNET) show that such multidisciplinary, international focused exchange programmes are effective to trigger awareness raising and preventive actions.